2017
DOI: 10.1051/e3sconf/20172200208
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of anaerobic digestion efficiency with use of mechanical excess sludge disintegration in the context of increased energy production in wastewater treatment plants

Abstract: Abstract. The main goal of the study was to evaluate the effects of mechanical sludge disintegration for enhancing full scale anaerobic digestion of municipal sludge. Batch disintegration tests and lab dewatering tests were also performed aiming at determining the release of organic compounds and assessing the impact of disintegration of excess sludge before the fermentation process of mixed sludge on the dewaterability of post-fermented sludge, respectively. In the study a disc disintegrator driven by a motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also new applications of hydrodynamic cavitation are beginning to emerge in other fields such as enhancing biogas production from WAS (Dular et al 2016). -Sudoł et al (2017) showed that with the increase in energy consumed in disintegration, the increased amounts of organic compounds were released from the sludge. It was also documented that the introduction of WAS disintegration prior to the fermentation tank, resulted in 33.9% increase in the biogas production (Moss et al 2013).…”
Section: Sludge Pre-treatmentmentioning
confidence: 99%
“…Also new applications of hydrodynamic cavitation are beginning to emerge in other fields such as enhancing biogas production from WAS (Dular et al 2016). -Sudoł et al (2017) showed that with the increase in energy consumed in disintegration, the increased amounts of organic compounds were released from the sludge. It was also documented that the introduction of WAS disintegration prior to the fermentation tank, resulted in 33.9% increase in the biogas production (Moss et al 2013).…”
Section: Sludge Pre-treatmentmentioning
confidence: 99%
“…The possibility of biological activity in sewage sludge must be considered when it is used. As a result, a great deal of study has been done on sewage sludge deactivation and stabilisation [3][4][5][6][7][8] through many different thermal utilisation routes: thermal hydrolysis [9], hydrothermal carbonisation (HTC) [10][11][12], HTC integrated with anaerobic digestion [13,14], torrefaction [15,16], pelletising [17], pyrolysis and co-pyrolysis [18,19], gasification [20][21][22][23], and combustion [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dewatering effluent's storage inevitably leads to water loss through evaporation, which nowadays is becoming an increasingly scarce resource in the agriculture sector during climate change [17][18][19][20]. Additionally, digestate still contains significant amounts of recalcitrant organic matter [21], which prompted many investigations regarding increasing its availability for further digestion to produce additional amounts of biogas [22][23][24][25][26]. Furthermore, nowadays higienisation of digestate or removal of ammonia is also considered as important issues [27,28].…”
Section: Introductionmentioning
confidence: 99%